Evaluation of a method for clinically assessing osteoarthritis of the knee. Issue 2 (February 1992) - Jones, A; Hopkinson, N; Pattrick, M; Berman, P; Doherty, M
Abstract : A system for assessing symptoms (pain, stiffness, gelling) and signs (local temperature, effusion, tenderness, synovial swelling, popliteal cyst, crepitus) of osteoarthritis of the knee has been developed. The system has been assessed for intra- and interobserver variation using normal and osteoarthritic knees. Intraobserver variability is low for all indices but interobserver variability is high for physical signs. It is suggested that the components within this system, when applied by a single observer, may provide a reasonable framework for clinical assessment of osteoarthritis of the knee.